(untitled) (Journal of Parents and Teachers, 2014)
Piercings are a topic of controversy, with some hoping that a new philosophy or lifestyle will emerge that will unite all piercing wearers. Others say it is too much pain or can lead to the spread of disease, as well as being an attention grabber. Find out what the author has to say about piercings and how he disputes each of the clichés in this article.